2000
DOI: 10.1006/jecp.2000.2589
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Working Memory: Exploring the Complementarity of Two Models

Abstract: The aim of the paper was to further explore the complementarity of the working memory models postulated by Pascual-Leone and Baddeley. Five-, six-, eight-and nine-yearold children were assessed on two working memory tasks, which have frequently been used within the respective streams of research: the Mr. Peanut task and the Corsi blocks task.Results indicated a developmental increase in spatial short-term memory for both tasks.Concurrent spatial suppression reduced performance on the two tasks in all four age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 44 publications
4
52
0
2
Order By: Relevance
“…Testing was terminated at this point. Each experimental series correctly recalled was given a score of one-third, and the thirds were added together to provide a span score (Barrouillet, Bernardin, & Camos, 2004;Kemps, De Rammelaere, & Desmet, 2000;Smith & Scholey, 1992). For example, the correct recall of all three series of one and two items and of two three-item series resulted in a span of 2.67 ([3 + 3 + 2 ] Â 1/3).…”
Section: Working Memory Span Tasksmentioning
confidence: 99%
“…Testing was terminated at this point. Each experimental series correctly recalled was given a score of one-third, and the thirds were added together to provide a span score (Barrouillet, Bernardin, & Camos, 2004;Kemps, De Rammelaere, & Desmet, 2000;Smith & Scholey, 1992). For example, the correct recall of all three series of one and two items and of two three-item series resulted in a span of 2.67 ([3 + 3 + 2 ] Â 1/3).…”
Section: Working Memory Span Tasksmentioning
confidence: 99%
“…The developmental trend for Working Memory is similar to the age-group differences found in earlier studies using the Corsi blocks test (a test with a similar format as the Tic Tac Toe test). These studies showed that adult levels of performance are not reached until adolescence (Hitch, Halliday, Dodd, & Littler, 1989;Issacs & Vargha-Khadem, 1989;Kemps, De Rammelaere, & Desmet, 2000;Wilson, Scott, & Power, 1987).…”
Section: Developmental Trends On Ef Component Tasksmentioning
confidence: 99%
“…Testing was terminated at this point. Each correctly recalled set counted as one third, and the thirds were added up to provide a span score (Kemps, De Rammelaere, & Desmet, 2000;Smith & Scholey, 1992). For example, the correct recall of all the sets of one, two, and three items, of two sets of four items, and of one set of five items resulted in a span of 4 [(3 ϩ 3 ϩ 3 ϩ 2 ϩ 1) ϫ 1/3].…”
Section: Materials and Proceduresmentioning
confidence: 99%